2022
DOI: 10.5455/azjcvs.2022.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Is there a relationship between thyroid hormone change and postoperative arrhythmia in patients undergoing coronary bypass surgery? A prospective randomized controlled trial

Abstract: Aim: Several factors are known to be associated with arrhythmias after cardiac surgery. This paper examines the changes in thyroid hormones after cardiac surgery and the relationship with arrhythmias. Material and Methods: A random sample of euthyroid patients scheduled for isolated coronary artery bypass surgery were recruited for a randomized prospective study. Patients were divided into two groups based on developing a new-onset arrhythmia (NOA) or atrial fibrillation (NOAF) after surgery (Group 2, n=18), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…Our study observed that the incidence of AF was significantly higher in FT3 Q1 group. Other study found that decreased tendency in FT3 values was prominent on the postoperative second day ( 20 ), our study also reported that AF occurred at day 2. These results indicated that lower FT3 level was strongly associated with AF.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our study observed that the incidence of AF was significantly higher in FT3 Q1 group. Other study found that decreased tendency in FT3 values was prominent on the postoperative second day ( 20 ), our study also reported that AF occurred at day 2. These results indicated that lower FT3 level was strongly associated with AF.…”
Section: Discussionsupporting
confidence: 84%
“…Previous systematic review demonstrated that preoperative factors including older age, creatinine level, worse cardiac function, hypertension and perioperative factors like perfusion time, use of inotropes and re-operation were associated with the risk of POAF following CABG ( 19 ). Other study monitored the dynamic levels of FT3 and found that decreased tendency in FT3 values was prominent on the postoperative second day, which is the most common day for arrhythmia following cardiac surgery ( 20 ). Interestingly, CABG-related euthyroid sick syndrome exerted detrimental effects on in-hospital adverse cardiovascular outcomes ( 21 ).…”
Section: Discussionmentioning
confidence: 99%